Vocabulary of Word Frequency in the Work “Романтики” by K. Paustovsky and a Few Observations on Its Language - Судавичене, Л. (Kalbotyra, 1977)
The present article is a continuity of the publications prepared by the Russian Language Department, Vilnius V. Kapsukas State University. in connection with the compilation of K. Paustovsky’s vocabulary as well as the writer’s vocabulary of word frequency. The article comprises the quantitative analyses of “Романтики” and the list of the most frequent words. Besides, the given list is compared with the analogous list of the most frequent words in the work “Дым отечества” by the same author.The comparison of the two lists revealed their almost complete correspondence which suggests a preliminary conclusion that the lists of the most frequent words compiled for different works by K. Paustovsky correspond by more than 68%, which means that the most frequent words of the language make up the basis of K. Paustovsky’s vocabulary.